Just murdered : a dead-end job mystery - Viets, Elaine, 1950- (Viets, Elaine, 1950- Dead-end job mystery series., 2005)
Helen takes a job at an upscale bridal salon. When a rich, obnoxious mother-of-the-bride is killed, Helen's fingerprints are found on the muder weapon -- a wedding dress.